2014
DOI: 10.1371/journal.pone.0091925
|View full text |Cite
|
Sign up to set email alerts
|

Constraints upon the Response of Fish and Crayfish to Environmental Flow Releases in a Regulated Headwater Stream Network

Abstract: In dry climate zones, headwater streams are often regulated for water extraction causing intermittency in perennial streams and prolonged drying in intermittent streams. Regulation thereby reduces aquatic habitat downstream of weirs that also form barriers to migration by stream fauna. Environmental flow releases may restore streamflow in rivers, but are rarely applied to headwaters. We sampled fish and crayfish in four regulated headwater streams before and after the release of summer-autumn environmental flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Considering that our trials utilised marbled crayfish females with attached and developing eggs, we believe that our findings are valid also for sexually reproducing species, thus covering both modes of reproduction. Our findings suggests that successful ontogeny under drought‐like conditions for this species is primarily related to the tolerance of crayfish eggs to periods without free water, which is well in line with adaptations of other drought‐tolerant species, such as construction of special aestivation burrows (Chester & Robson, ; Chester et al., ), burrow commensalism with other crayfish (Johnston & Robson, ), and digging deeper burrows to the water‐level during dry seasons (Horwitz et al., ; Riek, ). The tolerance to drought using various traits is probably crucial for inhabiting ecosystems with high water level fluctuations in freshwater crayfish.…”
Section: Discussionsupporting
confidence: 79%
“…Considering that our trials utilised marbled crayfish females with attached and developing eggs, we believe that our findings are valid also for sexually reproducing species, thus covering both modes of reproduction. Our findings suggests that successful ontogeny under drought‐like conditions for this species is primarily related to the tolerance of crayfish eggs to periods without free water, which is well in line with adaptations of other drought‐tolerant species, such as construction of special aestivation burrows (Chester & Robson, ; Chester et al., ), burrow commensalism with other crayfish (Johnston & Robson, ), and digging deeper burrows to the water‐level during dry seasons (Horwitz et al., ; Riek, ). The tolerance to drought using various traits is probably crucial for inhabiting ecosystems with high water level fluctuations in freshwater crayfish.…”
Section: Discussionsupporting
confidence: 79%
“…). Despite their small size, six of the streams are regulated by weirs for town water supply, reducing flows and often resulting in downstream reaches being completely dry over hundreds to thousands of metres (Mackie et al ., ), with impacts sufficient to cause the local extinction of some species (Chester et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…This process might increase fire impacts on crayfish aestivating in dry streambeds. The GNP region contains numerous water extraction points and reservoirs that alter stream flow regimes causing substantial negative impacts on algae, fish and invertebrates (e.g., Robson and Mitchell 2010;Chester et al 2014). Many of these impacts are associated with recolonization and movement processes of the biota, because weirs used for water extraction act as barriers to movement both directly and by creating sections of dry streambed immediately downstream (Mackie et al 2012;Chester et al 2014).…”
Section: Flow Regulationmentioning
confidence: 99%
“…The GNP region contains numerous water extraction points and reservoirs that alter stream flow regimes causing substantial negative impacts on algae, fish and invertebrates (e.g., Robson and Mitchell 2010;Chester et al 2014). Many of these impacts are associated with recolonization and movement processes of the biota, because weirs used for water extraction act as barriers to movement both directly and by creating sections of dry streambed immediately downstream (Mackie et al 2012;Chester et al 2014). Although another GNP study (at a different group of streams) showed that another species of Geocharax was resilient to drought and flow regulation (Chester et al 2014), this resilience was founded on the ability of this species to rapidly build aestivation chambers in stony streambeds.…”
Section: Flow Regulationmentioning
confidence: 99%
See 1 more Smart Citation